A 10-Year Risk Assessment and Primary Prevention Study of Atherosclerotic Cardiovascular Disease Among Adult Patients in Saudi Arabia: A Cross-Sectional Study - Abdulhameed Alkhalaf; Qasem Aljabr; Khalid Al Mulla; Duaa Almubarak; Abdul Sattar Khan; Zainab Y. Al Jaziri; Ibrahim Albahrani (Medicina)
Background and Objectives: Cardiovascular diseases (CVDs), primarily driven by atherosclerosis, are the leading cause of mortality worldwide. In Saudi Arabia, the prevalence of atherosclerotic cardiovascular disease (ASCVD) poses a significant public health challenge. To estimate the 10-year ASCVD risk among adults in Al-Ahsa, Saudi Arabia, and identify prevalent risk factors such as age, gender, diabetes, hypertension, smoking, cholesterol, and preventive medication use. Materials and Methods: This cross-sectional study included 58,743 adults aged 35–75 years from the Al-Ahsa Health Cluster. The ASCVD risk was calculated using the ACC/AHA Pooled Cohort Equations. Statistical analysis identified predictors of high ASCVD risk. Results: Most participants (76.3%) were at low ASCVD risk (≤10%), 13.3% at borderline to intermediate risk (10–19%), and 10.4% at high risk (≥20%). Smoking, diabetes (39.6%), hypertension (40.8%), and male gender were key predictors of high ASCVD risk. High-density lipoprotein (HDL) was protective, reducing ASCVD risk by 3%. Among high-risk individuals, 29.7% used aspirin, and 58.3% used statins. Conclusions: While most adults in Al-Ahsa are at low ASCVD risk, a significant portion remains at elevated risk. Modifiable risk factors, including smoking, diabetes, and hypertension, combined with statin and aspirin adherence, highlight critical areas for targeted interventions to reduce the ASCVD burden in this population.